Effect of Radial Neck Length on Joint Loading. (February 2019) - Berkmortel, Carolyn J; Gladwell, Michael S; Ng, Jennifer; Ferreira, Louis M; Athwal, George S; Johnson, James A; King, Graham JW
Introduction: Load transfer across the radiocapitellar joint of the elbow is poorly understood both in the setting of the native radial head and following radial head arthroplasty. The purpose of this in vitro study was to determine the effects of radial neck length, arm position, and lateral collateral ligament (LCL) repair on radial load.Methods: A uniaxial load cell was implanted into the radial neck of 8 cadaveric specimens that were mounted on an in vitro motion-control simulator and tested (in dependent, varus, and valgus arm orientations) with the native radial neck length and then −4 to +4 mm lengths. Testing was performed with the LCL intact and after sectioning and repair.Results: There was no significant difference between the 2 LCL states (P = .82), and LCL state was not protective of proximal radius overlengthening. Radial loads increased with increasing radial length (P < .001).Discussion and Conclusion: Overlengthening the radial neck resulted in higher compression forces, and underlengthening produced tensile forces, demonstrating that restoration of correct radial length during radial head arthroplasty is important to restore physiologic loading. In the varus position, tensile loading occurred, which may explain clinical problems with ingrowth of uncemented radial head implant stems and dissociation of bipolar implants.